Strategic capitalism : private business and public purpose in Japanese industrial finance - Calder, Kent E (Book collections on Project MUSE., 1993)
Was Japan's economic miracle generated primarily by the Japanese state or by the nation's dynamic private sector? In addressing this question, Kent Calder's richly detailed study offers a distinctive reinterpretation of Japanese government-business relations. Calder challenges popular opinion to demonstrate how Japanese private enterprise has complemented the state in achieving the national purpose of industrial transformation. Drawing on previously unexamined Japanese sources, he clearly shows the difficulties experienced by the government in picking potential industrial winners, together with its successes at the constructive but more limited tasks of providing public infrastructure, encouraging technological borrowing across industries, and promoting mixed public-private enterprises. While outlining the limits of Japanese government efforts to organize and transform economic life, Calder also highlights the important contributions of stable private sector partnerships between banking and industry: often relegating the state to a reactive brokerage role, keiretsu, or industrial groups, and Japan's long-term credit banks have fostered key infant sectors such as automobiles and electronics and have also systematically restructured declining industries. Strategic Capitalism is a book for all those interested in the formation of industrial policy, market-oriented yet public-spirited alternatives to bureaucratic guidance, and the true origins of Japan's global competitiveness.